Effect of the chemical composition of fillers in the filler–bitumen interaction. (1st February 2016) - Antunes, V.; Freire, A.C.; Quaresma, L.; Micaelo, R.
Highlights: All fillers tested showed an excellent performance in the water susceptibility test. f / b max is not directly dependent on filler's chemical composition. f / b max is not significantly affected by the bitumen. Δ T R&B can be bitumen-normalized with the bitumen temperature susceptibility. Abstract: In this study, the contribution of the chemical composition of the filler to the consistency and stripping resistance of filler–bitumen mixtures is analysed. The chemical composition and particle geometry of six fillers of different origins are related with the consistency of filler–bitumen mixtures, using four different binders. The fillers tested showed an excellent performance in the water susceptibility test, despite references of weak moisture resistance being made to asphalt with aggregates of the same petrology. The maximum filler content that may be mixed with the bitumen is a function of the filler's geometrical characteristics and not directly of their chemical composition. The consistency level defined in some paving materials specifications by way of the softening point increase can be bitumen-normalized with the bitumen temperature susceptibility, which may help to select the filler content in asphalt after the definition of new threshold values.